Stomach fluke infection in sahelian and West African dwarf small ruminants in Benin - Daga, Florian Dadjo (My University, 2012)
A cross-sectional study was carried out between December 2010 and November 2011 in order to determine the prevalence and the variation factors of the stomach fluke infection in small ruminants of Benin. The paunch and the honeycomb (rumenreticulum) of 366 sheep and 390 goats of West African Dwarf (WAD) or Sahelian breeds were selected from the two major agro-climatic areas of the country (Northern area and Southern area) and examined. The results showed an overall prevalence of 14.3% (108 infected subjects out of 756 examined) with 9 to 315 flukes per infected animal. Frequency and intensity of infections have been significantly (p <0.001) higher in wet seasons (27.35%) than in dries (3.61%). Three other associated factors (species, breed and origin) influenced notably (p<0.01) the infection rates. Then, the highest rate (26.06%) was recorded with Sahelian sheep followed by Sahelian goats (16.29%), WAD sheep (9.09%) and WAD goats (6.54%). Northern areas appeared as a favourable environment for the infection
Keywords: Paramphistomum; Epidemiology; Sheep; Goats; Benin